PENGEMBANGAN KURIKULUM DIKLAT PUBLIKASI ILMIAH SEBAGAI BENTUK FASILITASI PENINGKATAN KOMPETENSI GURU DALAM MENULIS BEST PRACTICE - Sri Sukarni Katamwatiningsih (Balai Diklat Keagamaan Semarang, 2020)
Abstract In the structure of the Scientific Publication curriculum it consists of 9 JP basic groups, 43 JP core groups and 8 JP support groups. In the education curriculum the supporting elements are the RTL training subjects, where training participants after completing the training are expected to be able to follow up on what has been obtained from the training material. But in implementing RTL, it does not yet have its own curriculum standard to be implemented by training participants. This research aims to develop a scientific publication curriculum, as a form of follow-up to the implementation of scientific publications, especially best practice. This research was conducted by the R & D Research method. In this trial participants were not required to write certain products but could choose according to the training participants' needs. From 10 training participants 5 people wrote best practices, so in this study focused on discussing best practice. In this study, the best practice training course was developed, in determining the allocation of time for each course of 15 hours of training. Each course can be elaborated according to the systematic writing of scientific papers.